2017
DOI: 10.1530/erc-17-0077
|View full text |Cite
|
Sign up to set email alerts
|

OP449 inhibits breast cancer growth without adverse metabolic effects

Abstract: Hyperinsulinemia is associated with a decrease in breast cancer recurrence-free survival and overall survival. Inhibition of insulin receptor signaling is associated with glycemic dysregulation. SET is a direct modulator of PP2A, which negatively regulates the PI3K/Akt/mTOR pathway. OP449, a SET inhibitor, decreases Akt/mTOR activation. The effects of OP449 treatment on breast cancer growth in the setting of pre-diabetes, and its metabolic implications are currently unknown. We found that the volumes and weigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 57 publications
0
13
0
Order By: Relevance
“…The upregulation of the SET oncogene has been has been described in several tumor models, and over time it has emerged as a promising molecular target for alternative therapeutic strategies in these cancers [23,24,25,26,27,28,29,30,31,32,33,34,35]. Our previous findings showed that PP2A inhibition is a frequent event in CRC, and we identified SET deregulation as a key mechanism to inhibit PP2A [8].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The upregulation of the SET oncogene has been has been described in several tumor models, and over time it has emerged as a promising molecular target for alternative therapeutic strategies in these cancers [23,24,25,26,27,28,29,30,31,32,33,34,35]. Our previous findings showed that PP2A inhibition is a frequent event in CRC, and we identified SET deregulation as a key mechanism to inhibit PP2A [8].…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, the use of SET antagonists such as OP449 and FTY720 have emerged in the last years as novel therapeutic approaches in human tumors with SET overexpressed and could also be useful in early-stage CRC patients. OP449 is a specific, cell-penetrating peptide against SET, which has shown anticancer properties in leukemia, prostate, breast and gastric cancers [18,35,42,43], but its potential usefulness in CRC remains to be evaluated. FTY720 is an immunosuppressant currently used in the sclerosis multiple, which has demonstrated potent antitumor effects in many cancers, including CRC [44].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although these compounds generally retain the amphiphilic, sphingolipid-like structure of FTY-720, no assumptions can be made about their off-target effects and safety profiles, and little information is yet available. Apolipoprotein E-derived peptides such as COG1410 also bound to SET, activated PP2A (Christensen et al, 2011) and exerted anti-tumor effects in several experimental models of cancer (Agarwal et al, 2014; Christensen et al, 2011; Fujiwara et al, 2013; Hu et al, 2015; Richard et al, 2016; Shlomai et al, 2017; Switzer et al, 2011). The precise mechanism of action and pathway to translation of these peptides are unclear.…”
Section: Pp2a and Cancermentioning
confidence: 99%
“…The female Rag1 −/− /MKR +/+ mice develop hyperinsulinemia but do not exhibit obesity, hyperglycemia or dyslipidemia [26]. Orthotopic tumor xenografts were performed in Rag1 −/− /MKR +/+ (Rag/MKR) mice and Rag1 −/− (Rag/WT) female mice using MDA-MB-231 cells, as previously described [34]. Tumors derived from the Rag/MKR mice were significantly larger and weighed more than those derived from the MKR tumors, as previously described [34] (Fig.…”
Section: Resultsmentioning
confidence: 99%